2012
DOI: 10.1155/2012/257374
|View full text |Cite
|
Sign up to set email alerts
|

Hypoglycemic and Hypolipidemic Effects of Ethanolic Extract ofMirabilis jalapaL. Root on Normal and Diabetic Mice

Abstract: The present study investigated the insulin sensitivity, hypoglycemic, and hypolipidemic activities of ethanolic extract of Mirabilis jalapa L. root (EEM) in normal and diabetic mice. After induction of diabetes with streptozotocin, both normal and diabetic mice were singly or repeatedly for 28 days administrated with EEM at doses of 2, 4, 8 g/kg, respectively. Before induction of diabetes, mice were administrated with EEM at doses of 2, 4, 8 g/kg for 14 days and were injected with streptozotocin and continued … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
19
0
1

Year Published

2012
2012
2019
2019

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 24 publications
(20 citation statements)
references
References 34 publications
0
19
0
1
Order By: Relevance
“…Different medicinal plants have been known for their anti-diabetic effects by a diversity of mechanisms by way of enhancing pancreatic β-cells regeneration, enhancing glucose dependent-insulin secretion in diabetic rats and improving insulin sensitivity [43]. A number of anti-diabetic herbs have been used for a long period for treatment of hyperglycemia and hyperlipidemia in different diabetic animal models [44,45,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…Different medicinal plants have been known for their anti-diabetic effects by a diversity of mechanisms by way of enhancing pancreatic β-cells regeneration, enhancing glucose dependent-insulin secretion in diabetic rats and improving insulin sensitivity [43]. A number of anti-diabetic herbs have been used for a long period for treatment of hyperglycemia and hyperlipidemia in different diabetic animal models [44,45,46,47].…”
Section: Discussionmentioning
confidence: 99%
“…STZ treated animals were provided a 5% glucose solution overnight to overcome drug induced hypoglycemia. After a 10 day period for development of diabetes, mice with moderate diabetes exhibit persistent glycosuria and hyperglycaemia (blood glucose >250 mg/ dL) were used for experiments (11).…”
Section: Methodsmentioning
confidence: 99%
“…Recently the study in our laboratory showed that trigonelline had a beneficial effect for diabetes through decreasing blood glucose and lipid levels, increasing insulin sensitivity index and insulin content, upregulating antioxidant enzyme activity, and decreasing lipid peroxidation [17]. Trigonelline also is one of the main components of Mirabilis jalapa L. root which possesses both potential insulin sensitivity and hypoglycemic and hypolipidemic effects on diabetes [18]. …”
Section: Introductionmentioning
confidence: 99%